Current status and future directions of application of urine proteomics in neonatology - Wu, Dan; Zhang, Lulu; Ding, Fangrui (Frontiers in Pediatrics, 2025)
With continuous advancements in mass spectrometry technology, researchers increasingly utilize this method to investigate the molecular mechanisms underlying various diseases, and to identify novel diagnostic and therapeutic strategies. Among proteomics applications, urinary proteomics stands out for its non-invasive nature, making it particularly suitable for vulnerable populations like neonates. This review provides a comprehensive overview of recent research on urinary proteomics in the field of neonatology. It summarizes findings from numerous studies, illustrating how urinary proteomic profiles provide critical insights into neonatal health and disease. By identifying specific protein biomarkers in urine, researchers can gain insights into the early detection and monitoring of neonatal diseases, potentially leading to more timely and effective interventions. As technology evolves, the sensitivity and accuracy of proteomic analyses are expected to improve, opening new avenues for research and clinical applications.